The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2005
DOI: 10.1002/mrdd.20050
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of infant cry: Acoustic cry analysis and parental perception

Abstract: Infant crying signals distress to potential caretakers who can alleviate the aversive conditions that gave rise to the cry. The cry signal results from coordination among several brain regions that control respiration and vocal cord vibration from which the cry sounds are produced. Previous work has shown a relationship between acoustic characteristics of the cry and diagnoses related to neurological damage, SIDS, prematurity, medical conditions, and substance exposure during pregnancy. Thus, assessment of inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
173
0
2

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 194 publications
(182 citation statements)
references
References 67 publications
4
173
0
2
Order By: Relevance
“…Contextually, human infants also produce extensive vocalizations when distressed or separated, and most observers readily accept that these sounds comprise a bout of 'crying.' Careful analysis of crying in human infants has shown that, while there is variability in the acoustic structure of cries according to the level of distress and some evidence in support of individual differences, the attributes that make up cry sounds are readily agreed upon and have been extensively documented in the literature (reviewed, e.g., by [51] and [111]). It seems reasonable to adopt a similar approach to the sounds of non-human mammalian infants, wherein the category of vocalizations made by distressed or separated infants would also be referred to as 'crying.'…”
Section: What Is 'Crying'?mentioning
confidence: 99%
See 1 more Smart Citation
“…Contextually, human infants also produce extensive vocalizations when distressed or separated, and most observers readily accept that these sounds comprise a bout of 'crying.' Careful analysis of crying in human infants has shown that, while there is variability in the acoustic structure of cries according to the level of distress and some evidence in support of individual differences, the attributes that make up cry sounds are readily agreed upon and have been extensively documented in the literature (reviewed, e.g., by [51] and [111]). It seems reasonable to adopt a similar approach to the sounds of non-human mammalian infants, wherein the category of vocalizations made by distressed or separated infants would also be referred to as 'crying.'…”
Section: What Is 'Crying'?mentioning
confidence: 99%
“…In humans, where crying has long been a subject of interest in the developmental psychology and pediatric literature, e.g. [51], [111] and [119], the responsiveness of the mother to an infant's cry has been studied in detail. In non-human primates, playback studies have shown that a squirrel monkey mother recognizes its infant, based solely on the individual acoustic characteristics of its cries [115].…”
Section: Crying and Parental Behaviormentioning
confidence: 99%
“…The signs and symptoms of ASD vary widely, especially the child's social communication development which is important for spotting early signs of ASD. Recently, there has been an increasing interest in vocal development of children with ASD and typically developing (TD) children, in particular crying (Esposito, Nakazawa, Venuti, & Bornstein, 2013;Esposito, Venuti, & Bornstein, 2011;Esposito & Venuti, 2009b, 2010bFort & Manfredi, 1998;LaGasse, Neal, & Lester, 2005;Manfredi, Bocchi, Orlandi, Spaccaterra, & Donzelli, 2009;Oller et al, 2010;Orlandi, Manfredi, Bocchi, & Scattoni, 2012;Reyes-Galaviz, Cano-Ortiz, & Reyes-García, 2008;Sheinkopf, Iverson, Rinaldi, & Lester, 2012;Venuti et al, 2012). Several studies reported that children with ASD express atypical patterns of distress vocalization such as higher fundamental frequency (f0),…”
Section: Crying In Typical and Atypical Developmentmentioning
confidence: 99%
“…A unidirectional microphone (Shure SM58; Shure Inc. Chicago, IL) was positioned at a fixed distance (25 cm 31,32 A CU is defined here as a high-energy voiced frame lasting at least 260 ms. This choice comes from literature where different time lengths are considered for CUs, ranging from 60 to 500 ms. 21,[33][34][35][36] In fact, CUs of very short duration do not allow the assessment of some relevant features such as their melodic shape.…”
Section: Recording Protocolmentioning
confidence: 99%
“…Thus, for classification, the same number of 1662 CUs was used for both groups, randomly selected in the TN group. On each CU, the following 22 attributes (parameters) that gained great scientific interest in the last years 31,33,41 were estimated (CU length is given in seconds, values concerning F 0 -F 3 in Hz): CU length, F 0 median, F 0 mean, F 0 standard deviation (F 0 std), F 0 minimum (F 0 min), F 0 maximum (F 0 max), number of estimated F 0 values,…”
Section: Features Extractionmentioning
confidence: 99%